2016
DOI: 10.3109/0886022x.2016.1144162
|View full text |Cite
|
Sign up to set email alerts
|

Simple blood and urinary parameters measured at ICU admission may sign for AKI development in the early postoperative period: a retrospective, exploratory study

Abstract: Recent studies have suggested that some blood physicochemical and urinary biochemical parameters have a standardized behavior during acute kidney injury (AKI) development. The changes in these parameters frequently begin to occur before significant rises in serum creatinine (sCr) and may help in identifying patients with more subtle decreases in glomerular filtration rate (GFR). Surgical patients have an increased risk of AKI but renal impairment is usually not evident at ICU admission. We hypothesized that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…FE K was analyzed in patients with different diagnoses in an intensive care unit, with No-AKI, transient and persistent AKI without renal replacement therapy. It was not altered by diuretic use [41]. In our study, FE K showed the highest accuracy by the AUC-ROC in predicting AKI diagnosis.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…FE K was analyzed in patients with different diagnoses in an intensive care unit, with No-AKI, transient and persistent AKI without renal replacement therapy. It was not altered by diuretic use [41]. In our study, FE K showed the highest accuracy by the AUC-ROC in predicting AKI diagnosis.…”
Section: Discussionmentioning
confidence: 60%
“…Although FE Ur and FE Na may be useful in differentiating between functional (pre-renal) and structural AKI (secondary to ischemia, toxins or both), the interpretation of these parameters remains conflicting [38,39,40,41]. Few studies have reported the performance of FE K in predicting AKI [40,41]. FE K was analyzed in patients with different diagnoses in an intensive care unit, with No-AKI, transient and persistent AKI without renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, biomarkers have their own limitations in predicting AKI as they are costly, and no single marker is specific and has slow turnaround time, making the diagnosis of AKI challenging in ICUs. 19 …”
Section: Introductionmentioning
confidence: 99%
“… 18 The same group demonstrated, in a retrospective analysis of postoperative patients, that while serum creatinine increases two days after ICU admission, higher fractional excretion of potassium values may appear as early as the day of admission, indicating patients at a higher risk of AKI. 19 Smyth et al estimated 24 hours urinary sodium and potassium excretion in 28,879 participants at high cardiovascular risk to conclude that urinary potassium excretion predicted clinically significant renal outcomes better than UNa. 20 …”
mentioning
confidence: 99%